'I assume they don't think!': teachers' perceptions of Normal Technical students in Singapore. Issue 2 (3rd April 2017) - Heng, Mary Anne; Atencio, Matthew
ABSTRACT: Teachers' attitudes and beliefs about students in a particular grouping hierarchy are shaped by their ideological views. Within education systems that have high international profiles, such as Singapore, what has been less explored is how teachers think about and interact with students who are seemingly positioned as being 'low‐ability' or 'low achieving' within disadvantaged education contexts. This paper accordingly examines teachers' perceptions of 'Normal Technical' students in Singapore. The findings underscore the need to understand teachers' interpretations and thinking about teaching and learning processes that influence classroom practice. This is a necessary starting point for pedagogical innovation and change in schools.